Treating attention problems in children exposed to intimate partner violence: Evaluating the Preschool Kids' Club. (September 2021) - Clark, Hannah M.; Galano, Maria M.; Grogan-Kaylor, Andrew C.; Stein, Sara F.; Graham-Bermann, Sandra A.
Highlights: The PKC reduced attention problems in children exposed to high levels of IPV. Trauma-specific interventions may effectively treat attention problems in high-risk children. High-risk children often do not respond to symptom-specific approaches for attention problems. More intensive treatment may be necessary to reduce attention problems in the long term. Abstract: Childhood exposure to intimate partner violence (IPV) increases risk for symptoms of inattention and hyperactivity, and yet no known evaluations of interventions for IPV-exposed children have demonstrated effectiveness in treating their attention problems. This study examined the utility of the Preschool Kids' Club (PKC), a treatment program tailored to the needs of preschool-aged children whose mothers had experienced IPV, in reducing children's attention problems during this critical developmental period. Participants ( N  = 120) were preschool-aged children who, with their mothers, participated in an eight-year randomized controlled trial (RCT) of the PKC. Longitudinal multi-level modeling was used to evaluate the main effect of intervention participation on children's attention problems, as well as moderating effects of IPV exposure and maternal depression. Although there was no main effect of intervention participation, children's outcomes were moderated by IPV exposure. Specifically, among children exposed to high levels of IPV, symptoms of inattention and hyperactivity were significantly lower for intervention participants than children in the control group one year post-intervention. These improvements were not sustained in the eight-year follow-up. Results provide support for the use of trauma-specific interventions for children exhibiting attention problems following exposure to high levels of IPV. However, more comprehensive and long-term treatment may be necessary to promote enduring change.